1988
DOI: 10.1007/bf00691239
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine kinase and lactate dehydrogenase changes following an eighty kilometer race

Abstract: Pre and post race serum malondialdehyde (MDA), creatine kinase (CK) and lactate dehydrogenase (LDH) levels were studied in runners following an 80 km (50 mile) race. MDA is an indicator of lipid peroxidation. Subjects averaged 47.4 years (range 35-60), had a mean maximal oxygen uptake (VO2max) of 48.2 ml/kg, and averaged 121 km (75 miles) per week in training. Throughout the race, runners maintained a pace approximating 72% of VO2max. Previous data from our laboratory indicated a high correlation between resti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
1
7

Year Published

1991
1991
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(67 citation statements)
references
References 17 publications
4
55
1
7
Order By: Relevance
“…The results of the present study showed that the serum concentration of MDA and CRP known as the markers of lipid peroxidation and cell damage respectively, keep on increasing in the subjects undergoing an intense and unaccustomed exercise. This is in accordance with the results from other investigators showing that plasma TBARs and CK levels increased after a 45 min session of flat treadmill running (Maughan et al, 1989;Kanter et al, 1988). Different studies by using various forms of exercise have reported significant increase in plasma levels of malondialdehyde (Bryant et al, 2003;Ramel et al, 2004;Rodriguez et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study showed that the serum concentration of MDA and CRP known as the markers of lipid peroxidation and cell damage respectively, keep on increasing in the subjects undergoing an intense and unaccustomed exercise. This is in accordance with the results from other investigators showing that plasma TBARs and CK levels increased after a 45 min session of flat treadmill running (Maughan et al, 1989;Kanter et al, 1988). Different studies by using various forms of exercise have reported significant increase in plasma levels of malondialdehyde (Bryant et al, 2003;Ramel et al, 2004;Rodriguez et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the release of CK was suppressed by the combined treatment of endurance training and GTE supplementation in an additive manner; moreover, there was a negative relationship between V O 2max improvement and increment of CK following exhaustive run. Because exercise-induce lipid peroxidation could increase membrane permeability and efflux of CK into the plasma (Kanter et al 1988;Maughan et al 1989), our results suggest that endurance training combined with catechins might better maintain membrane integrity and thereby increased oxygen consumption in muscle tissue.…”
Section: Discussionmentioning
confidence: 82%
“…Methods used to determine the possible effect of exercise on OSS in humans include the measurement of vitamin E levels (66)(67)(68), plasma levels of malondialdehyde (69), and effects on enzyme levels (68,(70)(71)(72).…”
Section: "Trap" Of Oiotfl~iids Atzd Effect Of Exercisementioning
confidence: 99%